Termografia como método auxiliar na identificação de nódulos de tireoide - Sebastião, Crislayne Keretch (2020)
Thyroid cancer is the most common neoplasm of the endocrine system and early detection of the disease increases the chances of successful medical treatment. Thermography has shown promising results in the detection of thyroid nodules, it is a painless, non-invasive method that does not use ionizing radiation and does not require contact with the patient’s body. This research aimed to analyze the thermal behavior of thyroid nodules using static thermography. Images of 32 volunteers with malignant or benign thyroid nodules, confirmed by ultrasound and fine needle aspiration, were evaluated at a teaching hospital specialized in cancer. The images were collected in an environment with a controlled temperature of 22 °C. The Fluke Thermography camera, Model Ti32, was used to take the images. The first image was acquired before the cold stress in the neck region (cooling with a gel bag for 30 seconds), and afterwards, they were acquired until the time of 10 minutes was completed (a total of 27 images for each patient). The analysis of the thermal images began using the Software Smart View 4.3, choosing the time image three minutes after the cold stress, as it represented the best moment of visualization of the nodules. Both the tumor areas (P0) and the adjacent region (healthy tissue – PS) were analyzed. Software R was used to extract the temperature from the analyzed regions. In the descriptive analysis of the sample, it was found that there was a predominance of female patients (28 women and four men) and the average age of the participants was 55,22 ± 11 years. Family history related to the thyroid was reported by 14 volunteers (43,75%) and among the cited comorbidities, the most reported disease was systemic arterial hypertension (31,25%) followed by diabetes mellitus (18,75%). As for the analysis of the images, 14 volunteers did not present categorization TIRADS (12) or ultrasound (2), and of the remaining 18 (56,25%), the ultrasound presented 38,89% of correctness in the correlation between the diagnoses of the ultrasound and the fine needle aspiration, with 11.11% being falsenegative results and 50% false-positive results. As for thermal images, the mean temperature of the benign nodules was 32,89 °C and in the malignant ones it was 34,43 °C, with a difference of 1,54 °C (p= 0,096). The analysis of the minimum temperature showed the best results, with a difference of 1,98 °C (p= 0,018) and there was practically no variation when analyzing the maximum temperature (0,03 °C). In the three-dimensional analysis, it was not possible to distinguish between malignant and benign nodules, within 3 minutes. The method was only able to distinguish the region with a nodule (greater concentration of hot spots) from the region with healthy tissue. Thus, further studies with thermography are still needed to help distinguish between the existing nodules. For future studies it is suggested to use dynamic thermography for this purpose.